Acceptance and needs of medication literacy education among children by their caregivers: A multicenter study in mainland China - Xu, Xiaolin; Wang, Zhonglan; Li, Xialei; Li, Ying; Wang, Yu; Wu, Xuexin; Hao, Lina; Wang, Xiaoling (Frontiers in Pharmacology, 2022)
Background: This study aims to investigate the needs of child caregivers on popular healthcare science works regarding the safe usage of children's medication, explore the characteristics of parents' demand for safe medication usage science, as well as the shortcomings of the current popular healthcare science works, and seek better coping strategies. Methods: A questionnaire was designed based on Lasswell's "5W" communication model to investigate the needs of child caregivers in terms of content, channels, and forms of popular healthcare science on the safe usage of children's medication. Results: The primary ways caregivers receive popular healthcare science education concerning safe medication usage knowledge are through medical institutions, notification by medical staff, and personal media. The caregivers of children have a high demand for the presentation of text, pictures, and videos in three forms of popular healthcare science content. Caregivers placed significant importance on the popularization of safe medication usage for children. The survey results showed that the top 3 ways for caregivers to think that the quality of popular healthcare science content was "very good" came from medical institutions, medical staff notifications, and personal media, effectively increasing popular healthcare information accuracy. The intelligibility and pertinence of content expression are urgently needed within the caregiver population. Conclusions: The public's demand for popular healthcare science shows a trend of diversification in terms of content and form. According to the individual needs of different groups, it was imperative to use different media platforms to broadly and quickly disseminate popular healthcare science content that has high accuracy and is easy to understand.